Landscape, Heritage and National Identity in Modern Europe - Renes, Hans. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book describes the way in which landscape and landscape heritage have been - and still are - used to define national identities. It shows how national narratives use different types of landscapes. Some nations use nature as their main point of reference, partly to circumcise conflicts between different ethnic groups. Other nations use agrarian landscapes, that are often describes as timeless and 'rooted'. Again other nations use history as a major sources for defining identities. In these cases, myths of origins, 'Golden Ages' or wars and conflicts deliver the materials for national narratives. The final section describes how nation states developed new urban as well as rural landscapes as national showpieces. As landscapes are an important but under-researched aspect of nation-building, this book fills a gap in the study of nationalism. Hans Renes retired in 2021 as a historical geographer at Utrecht University and professor of heritage studies at Vrije Universiteit Amsterdam, the Netherlands. He published on many different aspects of landscape history of the Netherlands and Europe as well as on the relation between landscape heritage and planning. He is co-editor of the Tijdschrift voor Historische Geografie and the recently launched Journal of European Landscapes. .
1. Introduction -- 2 Terminology: landscape, heritage, identity and nationalism -- 3. Natural Landscapes -- 4. Timeless Agrarian Landscapes -- 5. Cultural Landscapes and Deep History -- 6. Landscapes of Glorious Times -- 7. Landscapes of Conflict and Trauma -- 8. New Landscapes -- 9. Concluding Remarks. .
Keywords: Human ecology-History.; Civilization-History.; Europe-History-1492-.; Environmental History; Cultural History; History of Modern Europe